1988
DOI: 10.3171/jns.1988.69.4.0593
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin and the induction of intracranial arterial spasm

Abstract: Although a number of substances which participate in the physiological control of vascular caliber have been proposed to play a causative role in cerebral vasospasm, none of these has been shown to induce the profound, sustained degree of constriction or the vasculopathy that characterize this disorder. The present study was undertaken to determine whether bilirubin, a hemoglobin breakdown product with detergent-like activity, accrued in incubated blood or in intracranial hematoma and whether topical applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…It is relatively well known that the spinal fluid of the subarachnoid haemorrhage patients was vasoactive and cytotoxic [2,10,37], but only recently were the BOXes reported in the haemorrhage patients' spinal fluid [38]. Interestingly, increased bilirubin in the spinal fluid of the subarachnoid haemorrhage patient has a time course that is similar to the reported incidence of vasospasm [8,47].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It is relatively well known that the spinal fluid of the subarachnoid haemorrhage patients was vasoactive and cytotoxic [2,10,37], but only recently were the BOXes reported in the haemorrhage patients' spinal fluid [38]. Interestingly, increased bilirubin in the spinal fluid of the subarachnoid haemorrhage patient has a time course that is similar to the reported incidence of vasospasm [8,47].…”
Section: Discussionmentioning
confidence: 70%
“…Bilirubin levels rise in the spinal fluid following subarachnoid haemorrhage [31] and their time course correlates well with the accepted time course of cerebral vasospasm, but bilirubin is not vasoactive. Thus there has been an interest in bilirubin's association with vasospasm, though with mixed results [3,4,8,9,27,28,30,32,38,47]. A bilirubin derivative such as BOXes is therefore quite consistent with the clinical characteristics of vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that the concentration of L-PGDS in CSF increased transiently in patients with SAH in the acute stage and suggested that the purified L-PGDS from the CSF of SAH patients bound bile pigments such as biliverdin and/or its analogs, the metabolites of hemoglobin (Inui et al, 2002;Mase et al, 1999). In addition, the oxidative degradation products of bilirubin and/or biliverdin are one of the causes inducing the delayed vasospasm in patients with SAH (Clark et al, 2002;Kranc et al, 2000;Duff et al, 1988). These lines of evidence suggest that L-PGDS is expected to be a scavenger of the bile pigments that accumulate in the CSF with SAH.…”
Section: Discussionmentioning
confidence: 98%
“…The weight of evidence suggests that the primary agents are derived from the hematoma itself1 and from the red blood cell in particular.2'3 In addition to extensive documentation of the vasoactivity of oxyhemoglobin,4-7 several reports have indicated that bilirubin, a hemoglobin breakdown product, is capable of producing constriction of cerebral arteries, both in vivo and in vitro. 4,8,9 One part of this study was undertaken to determine the levels of bilirubin in subarachnoid clot. The remainder of the study focused on the mechanisms of bilirubin-induced vasocontraction.…”
mentioning
confidence: 99%